ДИСКУРС ТАЛҚЫЛАЎ ЖАНРЛАРЫН ОҚЫТЫЎДА БАҲАЛАЎ ӨЛШЕМИ ӨЗГЕШЕЛИКЛЕРИ: «PRESETT» (КЕЛЕШЕК ИНГЛИС ТИЛИ ОҚЫТЫЎШЫЛАРЫН ТАЯРЛАЎ ПРОЕКТИ) ТӘЖИРИЙБЕСИНЕН - Мамырбаева, Д.; Даўлетмуратова, Х. (SCIENCE and SOCIETY, 2016)
The article deals with the alternative methods of assessment on the subject Discourse analysis which is being taught on «PreSETT» program and its peculiarities in teaching English.